“Comportamiento agronómico del arroz (Oryza sativa L.) INIAP FL 1480, sometida a tres dosis de fertilización química, en la zona de Babahoyo”. - Morán Chávez, Karem Gissella (2019)
VIII. SUMMARY The present research work was carried out on the grounds of the Experimental Farm "Palmar", belonging to the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km. 7.5 of the Babahoyo-Montalvo road. The experimental zone has a humid tropical climate, with average annual temperature of 25 ° C, annual precipitation of 1845 mm, relative humidity of 74% and height of 8 m, with UTM coordinates 672954 and 9797115. The treatments consisted of rice varieties INIAP FL 1480 and INIAP 15 with chemical fertilization of 138 kg / ha of N, 69 kg / ha of P2O5, 90 kg / ha of K2O, 30 kg / ha of S20; 92 kg / ha of N, 46 kg / ha of P2O5, 75 kg / ha of K2O, 18 kg / ha of S20; 70 kg / ha of N, 23 kg / ha of P2O5, 30 kg / ha of K2O, 12 kg / ha of S20 and a control with fertilization carried out by the farmer. We used the design of Complete Blocks at random in factorial arrangement A x B, being the Factor A the varieties of rice, the Factor B the doses of chemical fertilization and 3 repetitions. For the evaluation and comparison of means of treatments, the Tukey test was used at 95% of probabilities. For the execution of the trial, all the practices and agricultural work that the crop requires for its normal development were carried out, such as land preparation, sowing, weed control, phytosanitary control, fertilization, irrigation and harvesting. Based on the results obtained, it was determined that the rice varieties respond adequately to the different doses of chemical fertilization; the conventional fertilization carried out by the farmer with 150 kg / ha of N, 60 kg / ha of P2O5 and 30 kg / ha of K2O promotes a late flowering of the crop; the rice variety INIAP 15 using 138 kg / ha of N, 69 kg / ha of P2O5, 90 kg / ha of K2O, 30 kg / ha of S20 influenced the agronomic characteristics of the rice crop as plant height, number of tillers and panicles / m2, panicle length, grains per panicles and weight of 1000 grains and the highest yield of the crop with 4462.2 kg / ha was reflected in the rice variety INIAP 15 applying 138 kg / ha of N, 69 kg / ha of P2O5, 90 kg / ha of K2O, 30 kg / ha of S20, as well as the highest net profit of $ 193.82. Key words: Behavior, dosage, chemical fertilization.